An Investigation Behavior Into Dental Biomechanical Analysis - Abbass, Sadiq Jafer; Ibrahim, Amal (Nahrain University College of Engineering Journal, 2008)
The aim of the study is to evaluate the Von Mises stress distribution of different human teeth model. Three-dimensional model of the maxillary central incisor, mandibular first molar and mandibular central incisor were constructed using Auto CAD (Auto CAD 2007) software and then imported to ANSYS software (ANSYS V.10) to get finite element model of each teeth. A loading simulating the 200N force was applied vertically and with different inclination to the crowns. Then same loading was applied vertically but the load was distributed along the incisal area for the incisors and at occlusal margin for the molar. Finally the crown was considered as porcelain material and the vertical load was distributed along each tooth and the Von Mises stresses were calculated. The results showed that the increase in the loading angle from 0°, 26° to 45° resulted in an increase in tooth Von Mises stress which means increase the probability of tooth failure. When the load distributed along wide region the ability of model to fail for the same loading will be decreased. Also when the crown consider as porcelain material there will be increasing Von Mises stress compare with the enamel crown for the same load region and load value